Strategic direction and institutional climate in teachers of an educational institution - Meza-Loreña, Ruth B. (2021)
The objective of the research was to establish the correlation that exists between the strategic direction and the institutional climate in the teachers of the Javier Pulgar Vidal Educational Institution, Utao 2019. The research level was correlational, and the applied type, non-experimental, cross-sectional design. The population was represented by all the teachers of the Javier Pulgar Vidal de Utao Educational Institution where the on-site sampling was carried out, being made up of 23 teachers. The instrument used was a survey and its instrument a questionnaire, validated by experts in the educational area, obtaining a reliability of 0.966 according to Cronbach's Alpha. The results for r = 0.9357 indicate a high and positive relationship, which determined a Degree of dependence = 87.55%; In other words, the establishment of a Strategic Direction in an educational institution fosters an institutional climate and it is concluded that there is a high positive relationship between Strategic Direction and Institutional Climate among the teachers of the Educational Institution Javier Pulgar Vidal, Utao 2019.